La protesi d’anca: anything new? - Aprato, A.; Greco, V.; Massè, A. (Lo Scalpello - Journal, 2019)
TOTAL HIP ARTHROPLASTY: ANYTHING NEW?Total hip arthroplasty has been described as “the operation of the 20th century”, thanks to the great outcomes, patientsatisfaction and improvement in their quality of life. In the last years, changes have been introduced in terms ofsurgical indications, approaches, tissue preservation, development of different implants, preoperative managementand postoperative protocols. The paper analyses different surgical approaches, in particular the anterior vs thepostero-lateral approaches; it focuses on surgical indications, either in younger or in older patients, as well as onimplants designs. Uncemented stems are frequently used in total hip arthroplasty; among these, short stems havegained space in the market in selected patients. They allow for preservation of the femoral neck, producing a morephysiological load pattern in the proximal femur and reducing stress shielding. In short-term follow-up, most of theshort stems provided survival rates similar to standard stems; however, long-term studies are not yet available. Theaim of this review is to summarise the advances in hip arthroplasty, the current literature on surgical approaches,stems design, biomechanical aspects and clinical outcomes associated mostly with the length of the femoral componentin primary hip replacement.